Review on experimental investigation of sediment erosion in hydraulic turbines - Rakish Shrestha; Rakish Shrestha; Prithivi Gurung; Prithivi Gurung; Sailesh Chitrakar; Sailesh Chitrakar; Bhola Thapa; Hari Prasad Neopane; Zhiwei Guo; Zhongdong Qian (Frontiers in Mechanical Engineering)
Sediment erosion in turbine materials is caused by various flow phenomena. The study of these phenomena can identify suitable measures to minimize their effect on the turbine. Various experimental test rigs have been developed alongside numerical analysis to study erosion and predict wear. In hydraulic turbines, erosion in Francis turbines is mostly seen at the guide vanes and runners, and in Pelton turbines, the needle and the bucket regions are the most vulnerable components. Prediction of wear due to erosion in various parts of the turbine is difficult, as wear depends on the properties of flow, base material, and sediment. Past studies have shown that the test rigs developed to investigate erosion have considered reducing the number of independent parameters to simplify the experiment. Erosion rates and wear patterns are predicted through both quantitative and qualitative methods. This article aims to conduct a systematic review of experimental setups and the results of those studies. This work is expected to be useful in understanding the vulnerable areas of erosion in hydraulic turbines and different mathematical relationships developed to quantify erosion, as well as to know the contemporary understanding in the sector of experimental investigation of sediment erosion.